MANAJEMEN KEARSIPAN DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI KANTOR DESA MUARA KECAMATAN TONRA KABUPATEN BONE - Amir, Sartika; Setiawati, Budi; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2023)
This study purposed s to determine the management of records in improving administrative services. at the Muara Village Office, Tonra District, Bone Regency. This study used in qualitative type using a descriptive type. The results of this study showed that archive management in improving administrative services at the Muara Village office (a) recording records at the Muara Village office was classified as good, (b) Control and distribution at the Muara Village office it had not run optimally because it did not use the disposition sheet for managing incoming and outgoing letters, (c) archive storage at the Muara Village office, namely by using the subject system by looking at the contents or about the letter (d) archives at the Muara Village office, it was maintained quite well in view of the fact that most of the archives were stored in a cupboard so that it was safe from the possibility of being damaged, burned, and wet, (e) the supervision of the Muara Village Head had also carried out quite good supervision in the field of archives, (f) transfer and the extermination at the Muara Village office had not run optimally because lack of understanding of employees in the transfer and destruction of archives and the absence of Standard Operating Procedure's at the Muara Village office.